Subconjunctival Loa Loa Worm: A Case Report - Afsar Saeed Shaikh, Ameena Ashraf, Mohammad Mateen Amir (Pakistan Journal of Ophthalmology, 2014)
A male patient 70 years old presented in outpatient department with a history of heaviness and irritation in his left eye for the last four months. He had been using different eye drops but there was no recovery. Slit lamp examination revealed a black subconjunctival mass 2-3 mm on surface. Removal under microscope revealed the mass was a worm about 3 cm and pathologist confirmed the worm was a dead Loa Loa. Laboratory report revealed eosinophilia of 8%. The patient also gave history of pruritis and swelling on medial side of thigh a year back. The patient showed marked improvement after 3 weeks. Key Words: Subconjunctival, Loa Loa Worm.